USING TOTAL WATER FOOTPRINT OF NATIONAL CONSUMPTION AS SUSTAINABLE DEVELOPMENT INDICATOR – A CRITICAL REVIEW - Andrei, Jean Vasile; Patrascu, Aurelia; Drăgoi, Mihaela Cristina; Gogonea, Rodica-Manuela; Zaharia, Radu Serban (Economics of Agriculture, 2018)
In highly competitive and modern economies, water represents a determinant productive resource and using the water footprint (WF) as a possible indicator in assessing sustainable development is integrated in the overall framework of macroeconomic efficiency analysis. The main aim of this paper is to argue that water footprint could represent a proper indicator in analyzing the sustainable economic development. In this context the territorial distribution of water footprint across the 28 EU countries is analyzed in order to substantiate decisions and achieve sustainable economic development forecasts and strategies at European level. The results have led to the conclusion that, overall, the total water footprint of national consumption in the 28 EU Member States has a very low degree of concentration, therefore, tends towards uniformity. With regard to the three types of water footprint, the main characteristic outcome of the research is the low degree of concentration for gray and green water footprint, while blue water footprint proves a moderate degree of concentration.